Damage in single lap joints of woven fabric reinforced polymeric composites subjected to transverse impact loading. (June 2015) - Choudhry, R.S.; Hassan, Syed F.; Li, S.; Day, R.
Abstract: Single lap joints of woven glass fabric reinforced phenolic composites, having four different overlap widths, were impacted transversely using a hemispherical impactor with different velocities in the low velocity impact range. The resulting damage was observed at various length scales (from micro to macro) using transmission photography, ultrasonic c-scan and x-ray micro tomography (XMT), in support of each other. These experimental observations were used for classification of damage in terms of damage scale, location (i.e. ply, interfaces between plies or bond failure between the two adherends) and mechanisms, with changing overlap width and impact velocity. In addition, finite element analysis was used to simulate delamination and disbond failure. These simulations were used to further explain the observed dependence of damage on overlap width and impact velocity. The results from these experiments and simulations lead to the proposal of a concept of lower and upper characteristic overlap width. These bounds relate the dominant damage pattern (i.e. scale, location and mechanism) with overlap width of the joint for a given impact velocity range. Highlights: Damage due to transverse impact on lap joints of woven GFRP is characterized. Main experimental techniques used are X-ray micro tomography and C-Scan. Damage is also modelled using finite element based cohesive zone model. Detailed discussion on interaction of damage mechanisms is presented. The study relates the dominant damage mechanism with overlap width of joint.